Individualizing Treatment for CMV with UL97 del597-599 Mutation: Beyond Unusual Response to a Lower Ganciclovir Dose Increase - Piedade, Ana; Vidal, Helena; Simões, Pilar; Vieira , Miguel Bigotte; Chasqueira , Maria Jesus; Caeiro, Fernando; Aires , Inês; Paixão, Paulo; Jorge , Cristina (Brazilian Journal of Transplantation, 2024)
Human cytomegalovirus (CMV) infection is the most prevalent infection affecting organ transplant recipients, and it is a cause of morbidity and mortality in patients undergoing kidney transplantation. The introduction of ganciclovir (GCV) for both prophylaxis and treatment has vastly improved patient outcomes. GCV resistance can be caused by mutations in the UL97 phosphotransferase gene or the UL54 polymerase gene. It occurs in 1 to 2% of kidney transplant recipients with CMV infection or disease. Antiviral resistance should be considered when increased viral loads and disease progression are observed despite the administration of adequate antiviral therapy. The degree of resistance varies depending on the type of mutation present. We report a patient with resistance to GCV due to a UL97 del597-599 mutation who, despite typically requiring an 8-fold increase in GCV dose, showed a significant decrease in viral load with just a double dose increase. However, the patient’s overall clinical course remained complicated. Due to severe leukopenia, maribavir had to be started, with a good response. Nevertheless, he ultimately died due to indirect CMV-related complications. This case also highlights the complexity of transplant patients, who present multiple challenges ranging from infections to therapy management.